Development of ratiometric fluorescent pH nanoprobe to study endocytic uptake pathways of antisense oligonucleotides - Liew, Donn Hou Feng (Nanyang Technological University, 2021)
Anti-sense oligonucleotides (ASOs) are single short strands of synthetic DNA/RNA designed to complement specific RNA sequences. Antisense therapy as a treatment option has received widespread consideration as only knowledge of a nucleotide sequence is necessary for drug design. However, one challenge of antisense therapy concerns attaining effective delivery to intracellular targets. Furthermore, the endocytic pathways taken by ASOs in different conditions are poorly understood. In this thesis, we have developed a ratiometric fluorescent pH nanoprobe to track antisense oligonucleotides (ASOs) as these ASOs negotiate different endocytic pathways in U2OS cells.